Mutation in porcine Zip4-like zinc transporter is associated with pancreatic zinc concentration and apparent zinc absorption - Siebert, Felicitas; Lühken, Gesine; Pallauf, Josef; Erhardt, Georg; Justus Liebig University Giessen (My University, 2013)
The aim of the present study was to analyse the sequence variability of the porcine Zip4-like Zn transporter gene and the association of identified sequence variants with average daily gain, apparent Zn absorption, plasma Zn concentration and Zn concentration in the liver and pancreas. For the purpose of the study, two different sample sets were used. Set one, which was used for sequencing and association analysis, included mRNA from intestinal tissue from thirty-five piglets of a feeding trial. Sample set two consisted of forty-six samples of genomic DNA from sperm or tissue of wild boars and several pig breeds and was used to genotype animals of different breeds. The sequence analysis of porcine Zip4-like complementary DNA in sample set one revealed the presence of seven nucleotide substitutions. Of these, six were synonymous, whereas a substitution of A with C in exon IX (XM_001925360 c.1430A > C) causes an amino acid exchange from glutamic acid to alanine (p.Glu477Ala). The association analysis revealed no influence of the six synonymous substitutions on Zn values, but the non-synonymous nucleotide exchange significantly increased Zn concentration in the pancreas and apparent Zn absorption of the piglets in week 2 of the feeding trial. The parentage of the piglets and the genotyping results in sample set two suggest a breed-specific presence of the A allele in Piétrain for this amino acid substitution. These results indicate that genotype influences the Zn absorption abilities of individual animals, which should be taken into consideration in animal breeding as well as for the selection of experimental animals.
Keywords: Zip4; SNP; zinc absorption; pigs; ddc:630